2018
DOI: 10.1002/lary.27572
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Recovery of Iatrogenic Vocal Fold Paralysis

Abstract: Objective To clarify the time course of recovery in patients with iatrogenic vocal fold paralysis. Study Design Retrospective chart review. Methods Medical records for all patients with iatrogenic vocal fold paralysis over a 10‐year period were reviewed to obtain demographic and clinical information, including onset of disease and recovery of vocal function. Stroboscopic exams of patients who recovered voice were reviewed blindly to assess return of vocal fold motion. Results One hundred and two patients of 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…Finally, the reproducible fitting of the vocal recovery data in iatrogenic vocal fold paralysis to the previously described recovery model further supports the notion that in focal axonal injuries, it is the severity of the RLN lesion, not the distance between the lesion and the larynx, that determines the time required for reinnervation . The time‐honored assumption that the farther the injury is from the larynx, the longer the time it takes to recover, has been challenged by theoretical modeling, experimental RLN injury in animal model, and clinical data . Paniello et al showed that a difference of 5 cm in RLN lesion location did not translate into a substantial difference in time to electromyographic recovery in a canine model of RLN injury.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…Finally, the reproducible fitting of the vocal recovery data in iatrogenic vocal fold paralysis to the previously described recovery model further supports the notion that in focal axonal injuries, it is the severity of the RLN lesion, not the distance between the lesion and the larynx, that determines the time required for reinnervation . The time‐honored assumption that the farther the injury is from the larynx, the longer the time it takes to recover, has been challenged by theoretical modeling, experimental RLN injury in animal model, and clinical data . Paniello et al showed that a difference of 5 cm in RLN lesion location did not translate into a substantial difference in time to electromyographic recovery in a canine model of RLN injury.…”
Section: Discussionmentioning
confidence: 59%
“…Paniello et al showed that a difference of 5 cm in RLN lesion location did not translate into a substantial difference in time to electromyographic recovery in a canine model of RLN injury. Tracy et al showed that the vocal fold motion recovery times between those with cervical injuries and thoracic injuries were comparable, a finding echoed by Husain et al The small difference between the median recovery times (2 weeks) in Tracy et al was much less than would have been expected based on the traditional 1 mm/day assumption for the speed of peripheral nerve regeneration, if the distance between the RLN lesion and the larynx determined the recovery time. It is more likely that longer times to recovery reflect more severe RLN injuries and the longer times it takes for repair across the injured segment.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations